Superhydrophobic platforms for the combinatorial analysis of biomaterials-cells interactions using arrays of 3D scaffolds with distinct mechanical and morphological properties - Oliveira, Mariana B. (2012)
High-throughput studies of cells mechanotransduction are usually performed using 2D biomaterials. However, cells-extracellular matrix interactions in the body occur in 3D environment. By using cells entrapped in hydrogels, it is not easy to isolate the mechanical effect from the chemical cues of biomaterials. We used a cytocompatible and non-expensive platform based in the patterning of wettable spots in superhydrophobic surfaces to deposit porous biomaterials in these regions. Freeze-dried alginate/chitosan scaffolds were used to create an array of mechanical properties and porosities. Adaptation of dynamic mechanic analysis equipment allowed performing on-chip single scaffold analysis. Micro-computed tomography allowed acquir- ing data for whole chips simultaneously. Results were validated using individual scaffolds and single-formulation chips. A sub-array with combined modulus/porosity properties was selected. Fibronectin (Fn) in different concentration was adsorbed in the scaffolds, and fibroblasts and osteoblast-like cells were seeded. The independent study of variables influence in cell response was performed by image-based methods. In the absence of Fn fibroblasts did not respond to mechani- cal properties in the chip range. Osteoblast-like cells showed higher cell adhesion in stiffer substrates. The adsorption of Fn was studied qualita- tively by image methods. Results related with Fn amount and scaffolds’ mechanical properties were analyzed for each cell type.